The Maximum Entropy Model with Continuous Features - Yu, Dong; Deng, Li; Acero, Alex (2008 NIPS Workshop, Whistler, BC, Canada, NIPS Workshop, Whistler, BC, Canada, 2008)
We present the maximum entropy (MaxEnt) model with continuous features. We show that for the continuous features the weights should be continuous functions instead of single values. We propose a spline interpolation based solution to the optimization problem that contains continuous weights and illustrate that the optimization problem can be converted into a standard log-linear one without continuous weights at a higher-dimensional space.